Differences in learning styles and life skills among secondary school students in East Jerusalem schools according to some demographic variables (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to identify differences in learning styles and life skills among secondary school students in East Jerusalem schools based on several demographic variables: gender, grade level, school type, and academic achievement level. The study employed a descriptive-analytical approach and was conducted on a sample of secondary school students in East Jerusalem schools. The researcher used two questionnaires to measure learning styles and life skills, after verifying their validity and reliability. Data were analyzed using means, standard deviations, independent samples t-tests, one-way ANOVA, and Tukey's post-hoc test. The results showed statistically significant differences in learning styles based on gender, favoring females, while no significant differences were found based on grade level. The results also revealed differences in life skills levels based on school type and academic achievement level, while no significant differences were found based on gender in some areas of life skills. The findings highlight the importance of considering individual and demographic differences in designing educational practices. This contributes to developing appropriate learning styles and enhancing students' life skills in a unique social and cultural environment, such as schools in East Jerusalem. The study recommends developing flexible teaching strategies that accommodate diverse learning styles and integrating life skills into curricula and classroom and extracurricular activities.
Keywords: Learning Styles; Life Skills; Secondary School; East Jerusalem; Demographic Differences